พฤติกรรมผู้บริโภคในการใช้บริการคลินิกทันตกรรมเอกชนในอำเภอเมืองเชียงใหม่ - ณัทกร เทพรัตน์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This study aimed to explore consumer behavior towards using services of private dental clinics in Mueang Chiang Mai. Samples were identified to 300 Thai consumers, who came to use services at the private dental clinics in Mueang Chiang Mai district at least once in the last 2 years. Questionnaires were used as the tool to collect data. Data analysis was conducted by the use of descriptive statistics, consisting of frequency, percentage and mean. The findings presented that most respondents were female, whose ages were equally found in 3 age-ranges: 15-24 years old, 25-45 years old and older than 45 years old. They were single with Bachelor’s degree and were student whose average monthly income was higher than 25,000 Baht. In addition, the results revealed that the majority took dental services at Kijja Dental Clinic. Their significant reason of using services from the private dental clinics was referred to the availability of modern and high-quality devices and appliances. The frequency in using services from the private dental clinics in the last 2 years was found between 3-4 times. Service that they mostly took from the private dental clinics was teeth cleaning. Reason influencing their decision making to take dental services from the private dental clinics was mentioned to oral and teeth health problems that needed to be treated. Their convenient date and time of taking services at the private dental clinics were in the evening of Saturday or Sunday, during 17.00-20.00 hrs. Most of them did not have right to claim for dental service charges; but for those who had the right to claim for it, their right was from the Social Security/Welfare State. They were mostly responsible for the dental service charges by themselves and mostly paid in cash. In each time of using dental services at the private dental clinics, they spent 500-1,500 Baht in average. Person influencing their decision making to use services at the private dental clinics was referred to the respondents themselves. They mostly made their visit to the clinics alone. Source of information where they learned about the private dental clinics was friend/family. They made decision to use services at the private dental clinics upon the recommendation from its previous consumers and the clinic that they chose was owned by the dentist who provided dental services. They had never changed their dental clinic. They were satisfied with its services. Therefore, for the next decision, they insisted on choosing the same clinic. The results of the study on service marketing mix factors showed that the top ten marketing mix that the respondents concerned on were as follows: offering dental services by specialists, service hygiene, quality of materials and medicines, proficiency of dentist in providing dental services, accuracy and safety along treatment process, quality of devices and appliances, personality and reliability of dentist, good odor in the clinic without smell of medicine, reasonable price comparing to quality and services, and new and modern devices.